Mr and Mrs Bull. looking over their Accounts. - Woodward, G. M. (George Moutard), ca. 1760-1809; Roberts, P.? (Roberts, P., 1802)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ceylon; Napoleon I, Emperor of the French, 1769-1821; John Bull (Symbolic character); Trinidad; Sri Lanka; Finance, Public -- Great Britain -- History -- 1688-1815; Ireland -- History -- Union, 1801